Cote d'Ivoire : Cancellation of the Extended Credit Facility Arrangement and Request for Disbursement Under the Rapid Credit Facility. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The prolonged crisis and violent conflict led to considerable destruction of private and public property, loss of life, and many refugees and internally displaced persons. Dealing with the shocks and aftermath of the post-election political crisis and armed conflict is a serious challenge for Cote d'Ivoire. Expenditure will need to be kept in line with available resources while addressing immediate priorities. The government's fiscal response to the economic crisis in the face of a very uncertain resource envelope is commended by Executive Directors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet